Strand Analysis, a free online program for the computational identification of the best RNA interference (RNAi) targets based on Gibbs free energy - Pereira, Tiago Campos; Bittencourt, Vinícius D'Ávila Pascoal; Secolin, Rodrigo; Rocha, Cristiane de Souza; Maia, Ivan de Godoy [UNESP]; Lopes-Cendes, Iscia (Sociedade Brasileira de Genética, 2007)
The RNA interference (RNAi) technique is a recent technology that uses double-stranded RNA molecules to promote potent and specific gene silencing. The application of this technique to molecular biology has increased considerably, from gene function identification to disease treatment. However, not all small interfering RNAs (siRNAs) are equally efficient, making target selection an essential procedure. Here we present Strand Analysis (SA), a free online software tool able to identify and classify the best RNAi targets based on Gibbs free energy (deltaG). Furthermore, particular features of the software, such as the free energy landscape and deltaG gradient, may be used to shed light on RNA-induced silencing complex (RISC) activity and RNAi mechanisms, which makes the SA software a distinct and innovative tool.
Keywords: RNAi; siRNA; siRNA design; software